Uji Aktivitas Antioksidan Ekstrak Etanol Buah Belimbing Wuluh (Averrhoa bilimbi L.): Antioxidant Activity Test of Ethanol of Belimbing Wuluh Fruits (Averrhoa bilimbi L.) - Elsa Akbar Wati; Fajar Prasetya; Juniza Firdha Suparningtyas (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2022)
Belimbing Wuluh (Averrhoa bilimbi L.) belongs to the Oxalidaceae family. The Bilimbi plant contains oxalate, phenol, flavonoid compounds which act as antioxidants and antibaterials. In previous studies Belimbing Wuluh has an antioxidant activity value of 91.89%. The fructus Bilimbi extracted by maceration method using 96% ethanol. The fructus Bilimbi purpose of this study was to determine the yield and the antioxidant activity of the ethanol extract from Bilimbi fructus this study resulted in a yield of 12% antioxidant activity tested by DPPH method (1,1 -diphenyl-2-picrylhydrazyl) from the extract various concentrations five replications of 100 ppm, 150 ppm, 200 ppm, 250 ppm, and 300 ppm. Then absorbance was measuring by UV-Vis spectrophotometry with maximum wavelength 516 nm. The antioxidant activity result showed that the IC50 value was 78,313 µg/mL. this indicaticates that the fructus Bilimbi exctract has strong antioxidant activity because it has an IC50 value less than 50 – 100 µg/mL.